ṬIBĀQ STYLES IN THE BOOK ‘UMDAH AL- AHKĀM MIN KALĀMI KHAIR AL-AN’ĀM (THE BALAGAH STUDY) - Azis, Abdul; Yusroh, Yusroh (Universitas Ahmad Dahlan, 2021)
This study aims to determine the á¹ibÄq language style used in the book Ê»Umdah al-AhkÄm min KalÄm Khair al-AnÄm and to analyze the types and forms of á¹ibÄq language style contained in it. The method used in this study is a qualitative method with observation and note-taking techniques in data collection. In analyzing the data used the method of agih with the basic technique of BUL (For Direct Elements). The data presentation used a qualitative descriptive method. The results of this study indicate that in the book Ê»Umdah al-AhkÄm min KalÄm Khair al-AnÄm there are 63 data with 61 hadith containing á¹ibÄq, of which 48 á¹ibÄq Ä«jÄb and 15 á¹ibÄq salab. á¹¬ibÄq Ä«jÄb in the form of fiÊ»il with fiÊ»il has 19 data, isim with isim is 21, the combination of fiÊ»il and isim has 2 data, and harf with harf have 6 data. While the form of á¹ibÄq salab which consists of fiÊ»il with fiÊ»il has 11 data, isim with isim has 3 data, and the combination of fiÊ»il and isim has one data.